Obstructive monitoring. Issue 4 (1st July 2020) - Finkle, Aaron; Shin, Dongsoo
Abstract: We consider a principal–agent relationship in which the principal's monitoring can be obstructive to the agent, reducing the agent's productivity. We show that, with obstructive monitoring, the optimal output schedule is distorted in all directions—the high‐cost agent produces less, and the low‐cost agent produces more than the first‐best levels. Moreover, if the principal has a choice, she will make monitoring deliberately obstructive, because when monitoring is obstructive, although the agent's productivity decreases, his information rent is extracted more effectively. We also show that obstruction is optimal even when the principal is unable to commit to her monitoring strategy ex ante.